PENGARUH KECERDASAN EMOSIONAL DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA - Junaidi Junaidi; Taufiq Taufiq (Jurnal Sains Riset, 2022)
The purpose of this study was to determine the effect of emotional intelligence and learning independence on the learning outcomes of class XI students of SMAN 1 Padang Tiji in the 2020/2021 school year. This type of research is ex-post facto. The population in this study were all students of class XI SMAN 1 Padang Tiji while the samples in this study were students of class XI IIS-1 and IIS-2, totaling 43 students. The sampling technique used was purposive sampling. Data collection was carried out using two instruments, namely a questionnaire (emotional intelligence and learning independence) and mathematics learning outcomes obtained through direct requests to mathematics teachers at SMAN 1 Padang Tiji. The data obtained were processed by statistical data processing program. The results of descriptive statistical analysis showed that the emotional intelligence of class XI students of SMAN 1 Padang Tiji was in the very high category with an average score of 121.93 with the highest score of 141 and the lowest score of 63. The learning independence of class XI students of SMAN 1 Padang Tiji was categorized very high with an average score of 98.07 with the highest score of 112 and the lowest score of 69. While themathematics learning outcomes of class XI students of SMAN 1 Padang Tiji were categorized as poor with an average score of 67.21 with the highest score of 85 and the lowest score of 50. The results of the analysis Inferential statistics showed that the emotional intelligence variable affected the mathematics learning outcomes of class XI students by 12.2% and the independent learning variable affected the learning outcomes of class XI students at SMAN 1 Padang Tiji by 10.5%.Keywords: Emotional Intelligence, Independent Learning, Learning Outcomes.